Jovan Cvijic: Forefather of neotectonics - Marković Miroslav (Zbornik Radova: Geografski institut "Jovan Cvijić", 2003)
Neotectonic activity as crucial factor of geomorphological evolution represents nowadays widely reckognized fact. It is generaly believed and accepted that the study of neotectonics began during first half of the 20th century by Russian scientists in the former Soviet Union. Almost fifty years before the definition and development of neotectonics Jovan Cvijic, a highly distinguished scientific researcher, was making very detailed observations of the youngest tectonic activity in the Balkans. He used these observations to analyse and explain the evolution and characteristics of the contemporaneous topography. Nearly all of Cvijic's geological and morphological studies include detailed neotectonic investigations. Selected examples from Cvijic's glacial studies of the youngest tectonic activity throughout the Balkans are presented to illustrate the detailed nature of his observations and analyses. These examples clearly show that Jovan Cvijic is the true forefather of neotectonics.